Effect of Nitrogen Addition to Shielding Gas on Cooling Rates and in the Microstructure of Thin Sheets of Duplex Stainless Steel Welded by Pulsed Gas Tungsten Arc Welding Process - Betini,Evandro Giuseppe (2019)
The effect of the nitrogen content in the shielding gas and its effect on temperature distributions at the welded zone of thin sheets of duplex stainless steel have been evaluated. The duplex stainless steels have many features due to unique microstructural combination of austenite and ferrite grains. The phase balance can be easily shifted depending on the welding parameters. Two sheets were welded using pure argon and pure argon plus 2% of nitrogen as shielding gas. The thermal profile had shown that N2-supplemented shielding gas lead to higher peaks of temperature using similar welding parameters. Microstructural examination showed that the austenite phase in the weld increased with the presence of nitrogen in the shielding gas. The added nitrogen promoted primary austenite formation and slightly increases the microhardness at the solidified zone. Microhardness mapping and metallographic imaging presented information about microstructures, confirming the formation of secondary phases during thermal cycle in the temperature range 850 °C and 950 °C. Control of ferrite amounts in the welds is essential mainly to improve mechanical properties and corrosion resistance of welding zones.